Cyber Security Challenges and Solutions in Critical Infrastructure: A Systematic Review of Threat Spectrum, Systemic Vulnerabilities, and Multi-Level Protection Strategies - Dengkeng, Andi; Halid, Agus; Pratiwi, Gita; Rachman, Andi Ikmal; B, Suriansyah; MZ, Luqman fanani (Newinera Publisher, 2025)
Digital transformation has increased operational efficiency infrastructure critical, but at the same time also open new loophole against attack increasingly complex and destructive cyberspace. This study aims to identify spectrum threat cyber targeting infrastructure critical, analyzing vulnerability accompanying systemic, as well evaluate strategy multi-level protection used in mitigation risk cyber. Using approach qualitative through review methods systematically, this study examines 20 primary sources in the form of scientific journals, policy reports, and studies. case international published 2015–2024. The research results revealed that threats such as ransomware, Advanced Persistent Threats (APT), attacks AI -based, and zero-day exploits are becoming a form of attack dominant, with energy, health, and communications sectors as the main targets. Vulnerabilities systemic found in aspects of old technology that is not updated, governance weaknesse, as well as low awareness cyber at the level operational. Strategy effective protection nature layered, including perimeter security, access management, data encryption, training awareness, to response incidents and system recovery. This study recommends integration strategy adaptive, data -based protection risk, and supported by policies strong national to strengthen resilience cyber sector infrastructure critical.